2017
DOI: 10.19182/bft2017.331.a31322
|View full text |Cite
|
Sign up to set email alerts
|

How Have Environmental Concepts Reshaped the Agroforestry Concept?

Abstract: Environmental sciences and concepts have evolved a great deal in the last three decades. This study aims to account for the way environmental concepts have changed and to describe the conse- quences for the concept of agroforestry. The study is based on a bibliometric ana- lysis carried out on the Web of Science, and summarizes the literature collected on the subject. Examples are given to support the analysis: agroforestry-based coffee-growing in the Western Ghats in India, cocoa in Ivory Coast and jungle rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…O Sistema de produção agroflorestal é uma prática antiga, desde tempos imemoriais e bem característica de uso como meio de produção e sobrevivência em comunidades tradicionais em várias partes do mundo, especialmente nos trópicos, sendo muitas vezes constituídos de forma casual, sem um arranjo produtivo ou delineamento previamente estabelecido (NAIR, 1993;MAZUCHOWSKI, 1994;AMADOR, 2003;BARISAUX, 2017).…”
Section: Sistema Agroflorestal (Saf)unclassified
“…O Sistema de produção agroflorestal é uma prática antiga, desde tempos imemoriais e bem característica de uso como meio de produção e sobrevivência em comunidades tradicionais em várias partes do mundo, especialmente nos trópicos, sendo muitas vezes constituídos de forma casual, sem um arranjo produtivo ou delineamento previamente estabelecido (NAIR, 1993;MAZUCHOWSKI, 1994;AMADOR, 2003;BARISAUX, 2017).…”
Section: Sistema Agroflorestal (Saf)unclassified
“…São condutores à estabilidade e podem mitigar os impactos causados pelo manejo insustentável de produção agrícola contemporânea (DE FREITAS et al, 2018). Isso ocorre em função de que promovem a cobertura do solo, aumentam a ciclagem de nutrientes e diminuem a depleção de minerais, incrementando a produtividade do sistema agropecuário (BARISAUX, 2017;CANUTO, 2017). Um tipo estratégico de SAF são os quintais agroflorestais que, localizados próximo às residências possuem multipropósitos e representam uma resistência ao modelo preponderante, garantindo segurança nutricional e alimentar bem como, promoção de geração de renda e sustentabilidade no uso da terra (MBOW et al, 2014).…”
Section: Introductionunclassified
“…There are many studies reviewing various aspects of intercropping, including yield stability [24][25][26], water and nutrient utilization [27][28][29][30][31], biodiversity [32][33][34][35][36][37][38][39], allelopathy [17,[40][41][42][43][44], agroforestry [29,[45][46][47][48][49][50][51], or species-dependent intercropping such as cereallegume or maize-based intercropping [7,31,52,53]. However, no study has investigated the overall research tends and features of intercropping.…”
Section: Introductionmentioning
confidence: 99%
“…However, no study has investigated the overall research tends and features of intercropping. Previous studies [45][46][47][48]54,55] have shown that scientometrics is a powerful tool for quantitative and statistical demonstration of research trends and features of a certain topic. The objective of this study is to quantitatively analyze the growth and evolution of intercropping research based on the scientometric method based on the Web of Science database.…”
Section: Introductionmentioning
confidence: 99%